2016
DOI: 10.1007/s41134-016-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

Stunting in India: An Empirical Approach to Human Rights-Based Solutions

Abstract: This study was undertaken to understand the relationship between poor sanitation and hygiene, clean drinking water, toilet use, mother's education, and religious practices and stunting. A human rights theoretical framework was utilized for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
1
0
3
Order By: Relevance
“…The regression results show that this variable has a statistically significant effect on stunting status with an OR value smaller than 1, which means that under-five children living in a household with piped water drinking water sources have a lower risk of stunting than under-five children with other sources of drinking water. This is consistent with a study conducted in India in by Parekh and Pillai (2016), which discovered that households without access to piped water had a higher rate of stunting. According to their findings, children with access to piped water are 20% less likely to be stunted than children without such access.…”
Section: Source: Ifls5supporting
confidence: 92%
“…The regression results show that this variable has a statistically significant effect on stunting status with an OR value smaller than 1, which means that under-five children living in a household with piped water drinking water sources have a lower risk of stunting than under-five children with other sources of drinking water. This is consistent with a study conducted in India in by Parekh and Pillai (2016), which discovered that households without access to piped water had a higher rate of stunting. According to their findings, children with access to piped water are 20% less likely to be stunted than children without such access.…”
Section: Source: Ifls5supporting
confidence: 92%
“…The differences in the effects of religion on stunting may be attributed to the variations in values and norms that guide lifestyles and beliefs concerning health and well-being (Parekh and Pillai, 2016). In contrast to a past study that found a better nutritional status of urban children (Bharati et al, 2008), this study found that under-five children residing in rural areas had a lower chance of undernutrition, once socio-economic factors are controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…Upaya intervensi terhadap pendidikan perempuan tanpa memandang status social dan keagamaan, serta peningkatan fasilitas sanitasi yang baik sangat penting untuk mengurangi anak-anak yang terkena stunting. Sehingga dalam penelitian tersebut sangat menyarakan untuk melakukan edukasi gizi dan sanitasi dalam menangani permasalahan stunting yang terjadi (Parekh & Pillai, 2016). Semua ini sejalan dengan apa yang telah dilakukan oleh tim pengabdian Universitas Siliwangi.…”
Section: Gambar 3 Pemberian Edukasi Gizi and Sanitasi Oleh Bapak Suha...unclassified